Cognitive effects of two opposite teaching styles: expositive and guided-participative - Roselli, Néstor Daniel (2014)
Fil: Roselli, Néstor Daniel. Pontificia Universidad Católica Argentina. Facultad de Psicología y Psicopedagogía. Centro de Investigaciones en Psicología y Psicopedagogía; Argentina